Civil liability of internet providers and image protection (Revista do Tribunal Regional Federal da 3ª Região, 2018)
This article analyzes the current protection of the right to the image in the in- This article analyzes the current protection of the right to the image in the information society. It distinguishes between liability for own act and liability for act of third party regarding the placement of undue content on the internet. It points out that there are several types of internet providers, and there are also distinctions regarding the civil liability of various internet providers: backbone provider, access provider, hosting provider, content provider, search provider and e-mail provider. The text studies the civil liability of providers before and after the Law 12.965/2014, including the exceptions made by the Law 12.965/2014 to the general regime of civil liability of providers, that is, copyright and pornography of revenge.
Keywords: Right to image; personality rights; civil liability; internet; providers